Cytokines and soluble receptors of the interleukin-1 family in Schnitzler syndrome. (4th May 2019) - Migliorini, P; Italiani, P; Pratesi, F; Puxeddu, I; Boraschi, D
Abstract : Objectives : Schnitzler syndrome (SchS) is an autoinflammatory disorder characterized by chronic urticaria, fever, and monoclonal gammopathy. The success of interleukin-1 (IL-1) blocking therapies suggests a crucial role for IL-1 in disease induction. The aim of this study is to perform a comprehensive analysis of IL-1 family cytokines and soluble receptors in a group of SchS patients. Method : Three patients fulfilling the criteria for the diagnosis of SchS were recruited; 80 blood donors formed the control group. IL-1 family cytokines (IL-1α, IL-1β, IL-33, IL-18), soluble receptors (sIL-1R1, sIL-1R2, sIL-1R3, sIL-1R4), and antagonists [IL-1Ra, IL-18 binding protein (IL-18BP)] were measured by a multiarray enzyme-linked immunosorbent assay. Free IL-18 was calculated as the amount of IL-18 not inhibited by IL-18BP. Cytokine levels were compared by the Mann–Whitney test. Results : IL-18 and free IL-18 were increased in patients compared with controls (p = 0.005 and p = 0.0082, respectively), while IL-18BP levels were not different. IL-1α, IL-1β, and IL-33 were undetectable in both patients and controls. The soluble receptors sIL-1R1, sIL-1R2, and ST2/sIL-1R4, and the IL-1 antagonist IL-1Ra were all within normal ranges; sIL-1R3 was significantly lower in patients than in controls (p = 0.039). Conclusions : The data indicate that SchS is characterized by increased circulating levels of free IL-18, possibly leading to a higher activation of innate/inflammatory effector cells. At variance with other inflammatory diseases, the lack of increase in sIL-1R1 and sIL-1R2 and the decreased levels of sIL-R3 imply a failure in the counterbalancing mechanism aimed at inhibiting excessive IL-1β in tissues.